ДИАГНОСТИКА И ПРОФИЛАКТИКА ДИСБАКТЕРИОЗА КИШЕЧНИКА ПРИ ХИРУРГИЧЕСКОМ ЛЕЧЕНИИ ИШЕМИЧЕСКОЙ БОЛЕЗНИ СЕРДЦА - Д. Л. Кранин; Н. И. Фёдорова; С. П. Казаков; Д. А. Назаров (Архивъ внутренней медицины, 2014)
Interest in the problem dysbiotic disorders of the gastrointestinal tract increases in modern medicine, however, representatives of the microflora have been studied for over 100 years. Microbiocenosis intestine plays an important role in maintaining and restoring human health, which is particularly important in the postoperative period. Proved that surgical patients develop intestinal dysbiosis adversely affects the postoperative period: deteriorating quality of life as a result of abdominal pain, nausea, frequent urges to defecate or, conversely, as a result of a tendency to constipation . The article describes the characteristics evolved dysbiotic conditions in patients after surgical treatment of coronary heart disease. The results of the application of probiotics in these patients, demonstrated the efficacy of the selected combination of probiotics in the normalization of intestinal microflora in the postoperative period.